2022
DOI: 10.1177/20503121221127096
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of refractive errors among school students in Ethiopia: A systematic review and meta-analysis

Abstract: Objective: Refractive errors are most common ocular disorders among children and adolescents. They remain as secondary causes of avoidable blindness in impoverished areas in Africa, most notably in Ethiopia. The problem worsens if it is not managed and addressed early. The aim of this systematic review and meta-analysis was to determine the prevalence of refractive errors among school students in Ethiopia. Methods: We searched international databases such as PubMed/Medline, Web of Science, CINAHL, Embase, Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 77 publications
(98 reference statements)
1
3
0
Order By: Relevance
“…The finding of this meta-analysis (5.26%) is consistent with the results of meta-analyses done in children in India in 2018 (5.3%) 60 and Nepal in 2023 (7.1%). 61 It is also in line with the result of a meta-analysis of childhood myopia and myopia in school children in Africa in 2022 (4.7%) 12,62 and comparable with the study finding in Ethiopia among school students (5.10%), 13 based on the results of 16 articles. The similarity in the study results may be due to approximate similarities in the study populations specifically their age.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The finding of this meta-analysis (5.26%) is consistent with the results of meta-analyses done in children in India in 2018 (5.3%) 60 and Nepal in 2023 (7.1%). 61 It is also in line with the result of a meta-analysis of childhood myopia and myopia in school children in Africa in 2022 (4.7%) 12,62 and comparable with the study finding in Ethiopia among school students (5.10%), 13 based on the results of 16 articles. The similarity in the study results may be due to approximate similarities in the study populations specifically their age.…”
Section: Discussionsupporting
confidence: 87%
“…In Ethiopia, the estimated prevalence of blindness and low vision due to URE was 7.8% and 33.4%, respectively. 45 Furthermore, the meta-analyses on the prevalence of REs among school students; the one conducted to estimate VI due to REs among children and adolescents, and the other stated VI among school children in Ethiopia reported 7.36% 13 and 6%, 46 and 6.13%, 47 respectively. However, those findings were based on a limited number of studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hospital-based study is also higher than several other community-based studies in Ethiopia, which have shown rates ranging from 4% to 12.9%. 18 , 29 , 30 This difference might also be explained by because of the study participants and study setting (ie, school children and the site of the study school).…”
Section: Discussionmentioning
confidence: 99%